The global burden of pediatric infective endocarditis (5–14 years): epidemiological patterns from 1990 to 2021 and projected trajectories - Xiao, Ying; Li, Yin; Hou, YuLing; Cheng, Zugen; Sun, TingTing; Liao, Yuan; Li, Yan (Frontiers in Cardiovascular Medicine, 2025)
BackgroundPediatric infective endocarditis (IE) remains a rare but life-threatening condition, with substantial morbidity and mortality among children worldwide. Despite advances in cardiac care and infection control, the global burden, temporal trends, and regional disparities of pediatric IE remain poorly characterized.MethodsWe conducted a comprehensive analysis of pediatric IE burden among children aged 5–14 years using the Global Burden of Disease (GBD) 2021 dataset. Annual incidence, mortality, and disability-adjusted life years (DALYs) attributable to IE were estimated across 204 countries and territories from 1990 to 2021. Analyses were stratified by sex, region, and socio-demographic index (SDI). An autoregressive integrated moving average (ARIMA) model was applied to forecast pediatric IE trends through 2035.ResultsGlobally, the incidence of pediatric IE declined by 27.6% (95% UI, −30.9% to −24.9%) and mortality by 21.4% (95% UI, −35.2% to −0.8%) between 1990 and 2021, with an estimated annual percentage change (EAPC) of −1.37% (95% CI, −1.49% to −1.24%) and −0.64% (95% CI, −0.75% to −0.54%), respectively. DALYs decreased by 19.2% (95% UI, −33.2% to 1.9%). Marked disparities persisted, with high-SDI regions, notably China, achieving the greatest reductions in burden, while sub-Saharan Africa and Eastern Europe exhibited stagnant or increasing rates. The ARIMA model projected a potential stabilization or slight rebound in the global pediatric IE burden by 2035, particularly among girls, although wide confidence intervals highlight the uncertainty of long-term forecasts.ConclusionsWhile significant progress has been made in reducing the global burden of pediatric IE, major geographic and socio-demographic inequalities persist. Sustained efforts to strengthen early detection, risk stratification, prevention (including rheumatic heart disease control and antibiotic prophylaxis), and equitable access to cardiac care are urgently required—especially in low- and middle-income countries. Enhanced surveillance and data collection will be crucial to monitor trends, evaluate interventions, and achieve further reductions in pediatric IE morbidity and mortality.